2014
DOI: 10.1089/ther.2014.0005
|View full text |Cite
|
Sign up to set email alerts
|

Wide Temperature Range Testing with ROTEM Coagulation Analyses

Abstract: Mild induced hypothermia is used for neuroprotection in patients successfully resuscitated after cardiac arrest. Temperature-dependent effects on rotational thromboelastometry (ROTEM(®)) assays with EXTEM(®), FIBTEM(®), or APTEM(®) in cardiac arrest patients have not previously been studied. Ten patients with out-of-hospital cardiac arrest who underwent induced hypothermia were studied during stable hypothermia at 33°C. ROTEM temperature effects on EXTEM, FIBTEM, and APTEM assays were studied at temperatures s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…This confirms previous findings stating that CPB‐induced clotting factor depletion and platelet dysfunction measured by ROTEM persisted after CPB and heparin neutralization . Others, however, stated that ROTEM revealed a hypocoagulative response to in vitro–applied hypothermia in blood reflected in the prolonged clot initiation and decreased clot propagation without affecting clot firmness . Changes of thromboelastometry parameters need to be interpreted with caution with respect to variations in hematocrit and platelet counts .…”
Section: Discussionsupporting
confidence: 89%
“…This confirms previous findings stating that CPB‐induced clotting factor depletion and platelet dysfunction measured by ROTEM persisted after CPB and heparin neutralization . Others, however, stated that ROTEM revealed a hypocoagulative response to in vitro–applied hypothermia in blood reflected in the prolonged clot initiation and decreased clot propagation without affecting clot firmness . Changes of thromboelastometry parameters need to be interpreted with caution with respect to variations in hematocrit and platelet counts .…”
Section: Discussionsupporting
confidence: 89%
“…TEG is a bedside test which allows assessment of the interaction between coagulation factors, platelets, fibrin and fibrinolysis. Routinely, TEG is performed at 37°C, nevertheless some studies were dedicated to test the influences of temperature on TEG measurements [27,28]. The results of the current TEG analysis under in vivo conditions demonstrated that application of MTH impaired both propagation of coagulation (a-angle), as well as K and MA, yet did not affect the R time.…”
Section: Discussionmentioning
confidence: 82%
“…As a standard feature, in most TEG studies blood tests were performed at 37°C, regardless of patient body temperature. This study examined whether the sample temperature had an impact on coagulation impairment during the TEG evaluation, similar studies has been performed for different patient groups with samples collected during MTH [27,31,35]. The MTH effects on coagulation tests from both in vivo (patient treatment) and in in vitro conditions (TEG) were analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…11,15 Another previous thrombolastographic study on hypothermic cardiac arrest patients found the relevance of temperature adjustments to be low. 14 We chose to perform ROTEM ® analyses at 37 • C as recommended by the ROTEM ® manufacturer because this provided the most reproducible results.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Thromboelastometric studies with in vitro induced hypothermia on whole blood from healthy volunteers have shown an association between impairment of coagulation and decreasing temperatures. 11,12 Only a few studies have investigated the effect of hypothermia on coagulation in cardiac arrest patients, [13][14][15] and some of these indicated a prolonged clot initiation during hypothermia. 13 To the best of our knowledge, no previous studies have investigated coagulation in cardiac arrest patients both during hypothermia and subsequent normothermia.…”
Section: Introductionmentioning
confidence: 99%